Health Risk Assessment of SO₂ and PM2.5 Exposure Among Parking Attendants in North Jakarta - Dewi, Putri Anggita; Pawitra, Aditya Sukma; Sari, Jayanti Dian Eka; Dinayah, Khuliyah Candraning (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
Air pollution has significant adverse effects on human health, particularly on the respiratory system. Prolonged exposure to pollutants such as fine particulate matter (PM₂.₅) and sulfur dioxide (SO₂) can lead to respiratory damage. Boulevard Raya Street in North Jakarta is an industrial area with heavy traffic, where parking attendants spend long hours outdoors and are continuously exposed to ambient air pollutants. This study aims to assess the health risk posed by PM₂.₅ and SO₂ exposure to parking attendants working along Boulevard Raya Street, Kelapa Gading, North Jakarta, in 2024. A quantitative approach was used, employing the Environmental Health Risk Analysis (EHRA) method with 18 respondents. Variables analyzed included gender, age, body weight, working hours, and exposure duration. The analysis showed that most respondents were aged between 18–50 years, with exposure durations of up to 8 hours/day, 350 days/year, over a 30-year period. The estimated average intake of PM₂.₅ was 10.88 mg/kg/day, with a Risk Quotient (RQ) of 1.83—indicating a potential non-carcinogenic health risk. In contrast, the average intake of SO₂ was 3.56 mg/kg/day with an RQ of 0.22, which falls within the acceptable safety threshold. In conclusion, PM₂.₅ exposure among parking attendants in the study area exceeds safe limits and poses a health risk, while SO₂ exposure remains within tolerable limits.